2019
DOI: 10.1177/0044118x19840048
|View full text |Cite
|
Sign up to set email alerts
|

Identifying as American Indian/Alaska Native in Urban Areas: Implications for Adolescent Behavioral Health and Well-Being

Abstract: American Indian and Alaska Native (AI/AN) youth exhibit multiple health disparities, including high rates of alcohol and other drug (AOD) use, violence and delinquency, and mental health problems. Approximately 70% of AI/AN youth reside in urban areas, where negative outcomes on behavioral health and well-being are often high. Identity development may be particularly complex in urban settings, where youth may face more fragmented and lower density AI/AN communities, as well as mixed racial-ethnic ancestry and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 60 publications
2
13
0
2
Order By: Relevance
“…Our results support the central hypothesis of the research (i.e., the collectivist and individualistic value orientations mediate the relationship between ethnic identity and the different dimensions of Lickan-Antay well-being), since total indirect effects of ethnic identity were found on well-being, mainly through collectivist orientations, but also through individualistic ones. As with studies carried out on other ethnic groups [ 16 , 17 , 18 ], this research confirmed that ethnic identity has a positive effect on well-being. Meanwhile, value orientations exerted a total mediating effect on the relationship between ethnic identity and two dimensions of Lickan-Antay well-being (i.e., internal harmony and social harmony) and a partial mediating effect with the other three dimensions of well-being (i.e., harmony in community life, harmony in ethnic-cultural development, and harmony in nature).This can be explained by considering that the process of development of ethnic identity influences the ascription to certain values, shared by the reference group [ 13 , 21 ] which, in turn, can positively or negatively influence well-being, depending on the context [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Our results support the central hypothesis of the research (i.e., the collectivist and individualistic value orientations mediate the relationship between ethnic identity and the different dimensions of Lickan-Antay well-being), since total indirect effects of ethnic identity were found on well-being, mainly through collectivist orientations, but also through individualistic ones. As with studies carried out on other ethnic groups [ 16 , 17 , 18 ], this research confirmed that ethnic identity has a positive effect on well-being. Meanwhile, value orientations exerted a total mediating effect on the relationship between ethnic identity and two dimensions of Lickan-Antay well-being (i.e., internal harmony and social harmony) and a partial mediating effect with the other three dimensions of well-being (i.e., harmony in community life, harmony in ethnic-cultural development, and harmony in nature).This can be explained by considering that the process of development of ethnic identity influences the ascription to certain values, shared by the reference group [ 13 , 21 ] which, in turn, can positively or negatively influence well-being, depending on the context [ 22 ].…”
Section: Discussionsupporting
confidence: 88%
“…Some authors [ 14 , 15 ] maintain that ethnic identity occurs as a conscious and free acceptance of this identity that necessarily involves reflection, the comparison of elements of their identity, and the development of a legitimate sense of belonging. Scientific evidence has shown a positive relationship between ethnic identity and well-being in different ethnic groups [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the literature demonstrated a lot of similarities with that addressing older Indigenous LGBQAþ people. Studies that do address all three identities often fail to provide analysis across all three identities as they intersect: being Indigenous and LGBTQAþ and young, with many of the studies only dealing with two of these dimensions (Brotman et al 2002;Evans-Campbell et al 2012;Elm et al 2016;D'Amico et al 2019;Brown et al 2019). Research on the mental health of LGBTQAþ people, for example, includes small Indigenous samples but does not always explore the responses of Aboriginal and/or Torres Strait Islander participants separately from the non-Indigenous ones (Hillier et al 2010;Robinson et al 2014;Smith et al 2014;Strauss et al 2017).…”
Section: Limitations Of Contemporary Approachesmentioning
confidence: 99%
“…Recounting historical trauma can provide a narrative framework for individuals and groups, connecting present‐day experiences and context to past traumas and thus influence health through psychosocial processes (Mohatt et al, 2014; Young, 2004). Public health researchers have recently called for research with Indigenous communities to pay more nuanced attention to this narrative process within Indigenous cultural contexts including how youth affiliate with group identity, individual and collective narratives of colonialism and historical trauma, and ways these meaningful frameworks may orient social action or behavioural outcomes (Brown et al, 2019; Trout et al, 2018; Wexler et al, 2009). For Indigenous communities, narratives at both the community and individual level can communicate adaptive capacity and resilience to historical trauma (Mohatt et al, 2014; Trout et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For Indigenous youth, cultural narratives of trauma provide individual and collective identity construction and thus may impact individual and community health (Trout et al, 2018). Indigenous youth who endorse an AI/AN cultural identity has been associated with better health outcomes, suggesting resilient effects (Brown et al, 2019). Storytelling has also been found to bring release and healing to AI adults experiencing historical trauma (Charbonneau‐Dahlen et al, 2016).…”
Section: Introductionmentioning
confidence: 99%